Morphological characteristics of soybean root apexes as indicators of soil compaction (Scientia Agricola, 2010)
Plant soil compaction poses a serious problem to agriculture because it produces different types of changes in plant characteristics. No method has been implemented to date to use root morphological changes as indicators of soil compaction levels. Therefore, the aim of the present study was to evaluate whether or not the morphological changes in root apexes of soybean (Glycine max (L.) Merrill) can be used as indicators of soil compaction levels. To this end, a silt-loamy soil material (from a Typic Argiudoll, Esperanza series), sieved through a 2 mm mesh was used and the following soil bulk density levels were determined: 1.1, 1.3 and 1.5 g cm³ for which the corresponding mechanical resistances were < 0.1, 0.5 and 3.5 MPa, respectively. The distance from the apex to the first tertiary root and the root diameter at 1.5 cm from the apex were measured on the secondary root apexes. A form factor equal to the quotient between these two variables was subsequently calculated. An inverse relationship between soil mechanical impedance and secondary root length and form factor as well as a direct relationship with the secondary root diameter were observed. Changes in rhizodermis cells were also recorded. The following morphological characteristics were found to evidence the highest sensitivity to soil compaction: i) the form factor, ii) rhizodermis papillose cells, iii) apical malformations in root hairs, and iv) root diameter in expansion areas. Taken together, the morphological characteristics of root apexes could be considered to be indicative of soil compaction.